PEMBUATAN KURVA ISODOSIS 2D DENGAN MENGGUNAKAN KURVA PERCENTAGE DEPTH DOSE (PDD) DAN PROFIL DOSIS DENGAN VARIASI KEDALAMAN UNTUK TREATMENT PLANNING SYSTEM - Nurul Ihya, Farhatin; Anam, Choirul; Gunawan, Vincensius (BERKALA FISIKA, 2013)
Treatment Planning System (TPS) is very necessary in radiotherapy planning to give the accurate radiation dose given to the patient.  In the TPS, 2D isodose curve is used to determine thedose distribution with the same rate at a certain distance from the radiation source.  The isodosecurve is obtained from the Percentage Depth Dose (PDD) and dose profile.  Measurement data ofPDD and dose profiles obtained from Kensaras Hospital in Semarang.  The PDD and dose profiledata were obtained from testing the water phantom for soft tissues such as muscles or other bodytissues.  Dose profile curve which is used  is at a various depth, such as: 1.5 cm, 5 cm, 10 cm, 15cm, 20 cm and 25 cm with an area of 5 x 5 cm2field, 10 x 10 cm2, 15 x 15 cm2, 20 x 20 cm, 30 x 30cm2 and 40 x 40 cm2.  At each depth of curve profile, the dose at the surface is calculated  andnormalized using  interpolation and normalized by narrowing techniques. 2D isodose curveobtained from the weighting technique to the calculation of the dose profile curve. In the field sizeof 5 x 5 cm2 and 10 x 10 cm2, isodose curve formed better in the absence of horn at the edge of thecurve.  In the field size larger than 10 x 10 cm2 there are horns on the edge of the curve at thelower depths.Keywords : Treatment Planning System (TPS),  2D Isodose curve, Percentage Depth Dose (PDD),Dose profile.